PEMAHAMAN NILAI PANCASILA MAHASISWA STIT DARUL HIJRAH MARTAPURA - Awad Awad; Mahridawati Mahridawati (Tarbawi, 2021)
Study on the Awareness of Pancasila Values Among Students at STIT Darul Hijrah Martapura for the Academic Year 2020/2021. The purpose of this research is to: describe the level of student awareness regarding the values contained within Pancasila, as well as to elucidate the connection between the values of Pancasila, particularly the second and fifth principles, with theories related to humanism and justice. In order to achieve the set objectives, this study utilizes a qualitative method. The research was conducted on 110 students of STIT Darul Hijrah Martapura by selecting samples from each semester. Methods used for data collection include interview sessions, questionnaire distribution, and document examination. Data analysis was carried out using qualitative descriptive techniques. Findings from this study indicate that: (1) students' understanding of Pancasila is in the moderate category. (2) there is a lack of relevance between the values of Pancasila and theories of humanity and justice.